A multi-viewpoint spectrum paradigm for inter-actor relationship analysis in non-social textual corpora: The case of the UN General Debate Corpus - Miller Efrat; Zhitomirsky-Geffet Maayan; Mitrani Mor (Journal of Data and Information Science, 2025)
This paper presents a new semi-automatic methodology for identifying inter-actor relationships by discerning viewpoints in non-social, political textual corpora. Although previous research has successfully discerned viewpoints, biases, and affiliations based on textual features, the task of relationship analysis in the absence of interactional data remains unaddressed.